Multi-species inversion of CH4, CO and H2 emissions from surface measurements - D. Hauglustaine; S. Szopa; F. Chevallier; P. Bousquet; I. Pison (Atmospheric Chemistry and Physics, 2009)
In order to study the spatial and temporal variations of the emissions of greenhouse gases and of their precursors, we developed a data assimilation system and applied it to infer emissions of CH4, CO and H2 for one year. It is based on an atmospheric chemical transport model and on a simplified scheme for the oxidation chain of hydrocarbons, including methane, formaldehyde, carbon monoxide and molecular hydrogen together with methyl chloroform. The methodology is exposed and a first attempt at evaluating the inverted fluxes is made. Inversions of the emission fluxes of CO, CH4 and H2 and concentrations of HCHO and OH were performed for the year 2004, using surface concentration measurements of CO, CH4, H2 and CH3CCl3 as constraints. Independent data from ship and aircraft measurements and satellite retrievals are used to evaluate the results. The total emitted mass of CO is 30% higher after the inversion, due to increased fluxes by up to 35% in the Northern Hemisphere. The spatial distribution of emissions of CH4 is modified by a decrease of fluxes in boreal areas up to 60%. The comparison between mono- and multi-species inversions shows that the results are close at a global scale but may significantly differ at a regional scale because of the interactions between the various tracers during the inversion.